2017
DOI: 10.15294/biosaintifika.v9i2.8722
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soybean Genotypes for Pod Shattering Resistance Associated with Agronomical and Morphological Characters

Abstract: A yield loss caused by pod shattering is one of the obstacles to the improvement of soybean productivity in tropical areas. The aim of this study was to identify the resistance of soybean genotypes to pod shattering as affected by agronomical and morphological characters. The field study was conducted in Malang, Indonesia, using 150 soybean genotypes. Data were collected on agronomical traits, the percentage of pod shattering, and pod morphological traits. Identification for shattering resistance was done as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Zhang and Bellaloui (2012) reported that different weather patterns, especially temperature and rainfall in a year could be essential factors affecting seed shattering patterns. Furthermore, the anatomical and morphological of the pod also reported determining the shattering resistant (Bara et al 2013;Krisnawati and Adie 2017;Zhang et al 2018). 3.1827 ** 0.1330 ** 16.51 Note: ** = significant at 1 % probability level (p < 0.01), ns = not significant, CV = coefficient of variation 1.96 Note: HR: highly resistant, R: resistant, M: moderately resistant, S: susceptible, HS: highly susceptible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang and Bellaloui (2012) reported that different weather patterns, especially temperature and rainfall in a year could be essential factors affecting seed shattering patterns. Furthermore, the anatomical and morphological of the pod also reported determining the shattering resistant (Bara et al 2013;Krisnawati and Adie 2017;Zhang et al 2018). 3.1827 ** 0.1330 ** 16.51 Note: ** = significant at 1 % probability level (p < 0.01), ns = not significant, CV = coefficient of variation 1.96 Note: HR: highly resistant, R: resistant, M: moderately resistant, S: susceptible, HS: highly susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…The selection method used for shattering resistance was an oven-dry method (Krisnawati and Adie 2017). When plants at R8 stage (leaves had started to turn yellow), three sample plants were randomly taken, and dried in the room temperature for three days in an upright position.…”
Section: Screening For Shattering Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to Arabidopsis and oilseed rape, where a mechanical test is the most common technique to measure pod firmness ( Morgan et al, 2001 ), the oven drying method is the most convenient and widely accepted assessment of pod shattering resistance in soybean. The test implemented during the course of these field trials was based on peer-reviewed published methods with minor modifications ( Funatsuki et al, 2014 ; Krisnawati and Adie, 2017 ; Krisnawatiorcid et al, 2020 ). First, harvested pod samples were allowed to equilibrate their moisture levels at room temperature.…”
Section: Methodsmentioning
confidence: 99%